2018
DOI: 10.1111/bcp.13780
|View full text |Cite
|
Sign up to set email alerts
|

The journey of metformin from glycaemic control to mTOR inhibition and the suppression of tumour growth

Abstract: Our knowledge of the effect of metformin on human health is increasing. In addition to its ability to improve the control of hyperglycaemia, metformin has been shown to reduce the burden o,f ageing via effects on damaged DNA and the process of apoptosis. Studies have shown that metformin may reduce the risk of cardiovascular disease through influences on body weight, blood pressure, cholesterol levels and the progression of atherosclerosis. Studies also suggest that metformin may be beneficial for neuro‐psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 84 publications
0
59
1
2
Order By: Relevance
“…A recent meta‐analysis that considered these and other studies concluded that cognitive impairment is significantly less prevalent in diabetic patients treated with metformin (odds ratio = 0.55, 95% CI 0.38–0.78), and dementia incidence is also significantly reduced (hazard ratio = 0.76, 95% CI 0.39–0.88; Campbell et al, ). As a whole, these studies clearly suggest that metformin can effectively counteract neuronal progressive degeneration and dementia; furthermore, it appears that metformin can offer protection also toward other age‐related diseases such as cardiovascular diseases and some types of cancer; therefore, life expectancy of metformin‐treated T2D patients can be higher than age‐matched nondiabetic controls (Amin, Lux, & O'Callaghan, ; Bannister et al, ; Barzilai, Crandall, Kritchevsky, & Espeland, ; Vancura, Bu, Bhagwat, Zeng, & Vancurova, ). For these reasons, metformin is going to be tested in the TAME trial on elderly persons with the final goal to evaluate its effects on cardiovascular events, cancer, dementia, and mortality (Barzilai et al, ).…”
Section: Is Metformin a Possible Candidate For Combating Ds Cognitivementioning
confidence: 99%
“…A recent meta‐analysis that considered these and other studies concluded that cognitive impairment is significantly less prevalent in diabetic patients treated with metformin (odds ratio = 0.55, 95% CI 0.38–0.78), and dementia incidence is also significantly reduced (hazard ratio = 0.76, 95% CI 0.39–0.88; Campbell et al, ). As a whole, these studies clearly suggest that metformin can effectively counteract neuronal progressive degeneration and dementia; furthermore, it appears that metformin can offer protection also toward other age‐related diseases such as cardiovascular diseases and some types of cancer; therefore, life expectancy of metformin‐treated T2D patients can be higher than age‐matched nondiabetic controls (Amin, Lux, & O'Callaghan, ; Bannister et al, ; Barzilai, Crandall, Kritchevsky, & Espeland, ; Vancura, Bu, Bhagwat, Zeng, & Vancurova, ). For these reasons, metformin is going to be tested in the TAME trial on elderly persons with the final goal to evaluate its effects on cardiovascular events, cancer, dementia, and mortality (Barzilai et al, ).…”
Section: Is Metformin a Possible Candidate For Combating Ds Cognitivementioning
confidence: 99%
“…Although metformin was initially identified as an anti-diabetic drug, its pleiotropic effects have been recognized over the past several years. Metformin is emerging as a drug with numerous beneficial effects that include body weight control; reduction of the risk for cardiovascular and neuropsychiatric disorders; and treatment of nonalcoholic fatty liver disease, metabolic syndrome and cancer (Zhou et al 2018, Amin et al 2019. The anti-cancer potential of metformin was first recognized in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the excessive activation of the mTOR (mammalian target of rapamycin) signaling pathway is closely related to cell metabolism, growth, and tumor proliferation. [ 20 ] Recent research indicates that metformin can inhibit tumor growth by affecting the mTOR pathway. mTORC1 is one of the complexes that contain the catalytic subunit, mTOR, which is essential for cellular proliferation and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%